PENGARUH PARENTAL BONDING TERHADAP IMPOSTOR PHENOMENON DIMEDIASI WELAS DIRI (SELF-COMPASSION) PADA MAHASISWA DI BANDUNG RAYA - Adinda Zhavira, - (2023)
Tujuan penelitian ini adalah mediasi welas diri (self-compassion) pada pengaruh parental bonding terhadap impostor phenomenon pada di Bandung Penelitian melibatkan 289 responden perempuan dan 107 responden laki-laki (N=396) yang diperoleh menggunakan teknik accidental sampling. Responden instrumen telah yang terdiri atas Self-Compassion 0,81 mengukur welas Parental Bonding Instrument dimensi parental care 0,87 dan dimensi parental control dengan reliabilitas 0,76 mengukur persepsi individu terhadap Parental Clance Impostor Phenomenon 0,89 mengukur gejala analisis jalur (path analysis) pengaruh parental bonding terhadap impostor phenomenon dimediasi welas diri pada di Bandung Penelitian bahwa welas diri dapat memediasi pengaruh parental bonding dimensi parental care dan parental control terhadap impostor phenomenon. The current study aims to investigate the relationship between the impostor phenomenon and self-compassion in adult students, while inspecting the latter variable's mediating role in the relationship between students' recollections of their parents' parenting styles and their current impostor expressions. The study comprised 289 females and 107 males (N=396) who completed online forms of the Clance Impostor Phenomenon Scale (CIPS; r=0.89), the Parental Bonding Instrument (PBI; r care=0.87; r control=0.76), and Self-Compassion Scale (SCS; r=0.81) which collected by accidental sampling. The participants' self-compassion was negatively correlated (at medium to strong size) with their impostor expressions. Perceived parental care was indirectly associated with the students' impostor expressions through self-compassion, meaning that the sample's students who perceived their parents as high caring exhibited lower impostor expressions because they were more compassionate. Also, perceived parental control was negatively associated with the students' impostor expressions through self-compassion. Namely, students who perceived their parents as more controlling had greater impostor expressions because they were less compassionate. The etiological significance and applied implications of these findings are discussed.